Analysis of research strategies to determine individual color preference: N‐alternative forced choice, rank‐order, rating and paired comparison. Issue 2 (26th December 2022) - Yu, Luwen; Yun, Chen; Xia, Guobin; Westland, Stephen; Li, Zhenhong; Cheung, Vien
Abstract: Exploring an efficient research method for understanding color preference is important to researchers and designers. This work compares four experimental methods for individual color preference research (N‐alternative forced choice, rank‐order, rating and paired comparison). Three psychophysical experiments were carried out with 338 participants. Participants were presented with six color patches (red, orange, yellow, green, blue and purple) arranged in a random order. This work suggested orange is the strongest preferred color and green is the weakest preferred using three individual color preference experimental methods with six hues. The Monte Carlo Analysis method further compares the result performance for four methods, which suggests the rating, paired comparison and rank‐order methods are more stable than the N‐alternative forced choice method when only a small number of participants take part in the experiment. For studies involving small numbers of participants (even less than 6), the rating, rank‐order and pair comparison methods should be preferred. Abstract : The rating, paired comparison and rank‐order method are more stable than the AFC method when only small number participants take part in the experiment, such as for studies involving small numbers of participants (less than 11 participants), the rating and rank‐order method should be preferred.